Lithium-doped silicon-based oxide negative electrode active material, method for preparing same, and negative electrode and secondary battery comprising same

By controlling the crystallinity of silicon-based oxides and introducing Li pretreatment technology, the problem of deterioration of battery life characteristics caused by volume expansion in the Si-based material in lithium secondary batteries is solved, and the energy density and battery stability are improved.

CN119764428APending Publication Date: 2025-04-04SK ON CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510073502.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-07-29
Filing Date
2021-05-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The graphite active materials commonly used in lithium secondary batteries have insufficient energy density due to low theoretical capacity. At the same time, the Si-based materials have deteriorated battery life characteristics due to volume expansion.

Method used

By controlling the crystallinity of silicon-based oxides and introducing Li pretreatment processes, battery stability and life characteristics are improved, and capacity characteristics are optimized by adjusting the ratio of lithium silicates.

Benefits of technology

The energy density and battery life of lithium secondary batteries are improved, the initial charging and discharging efficiency is improved, and the energy cost during Li pretreatment is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention provides a negative electrode active material including negative electrode active material particles, a method of preparing the same, a negative electrode, and a lithium secondary battery including the negative electrode active material, the negative electrode active material particles including: a silicon oxide (SiOx, 0lt; x < = 2); and at least one lithium silicate selected from the group consisting of Li2SiO3, Li2Si2O5, and Li4SiO4 in at least a portion of the silicon oxide, in which when a signal generated in a region of 200-600 cm-1 according to a Raman spectrum is deconvolved into three peaks, the absolute values of the wavenumber are set as peak A, peak B, and peak C, respectively, from the lowest to the highest of the absolute values of the wavenumber, and the negative electrode active material particles satisfy relational expression 1.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application is a divisional application of the Chinese invention patent application with the application date of May 10, 2021, application number 202110503604.8 and invention name “Lithium-doped silicon-based oxide negative electrode active material, preparation method thereof, negative electrode and secondary battery containing the same”. This application claims the priority of KR10-2020-0094407 (July 29, 2020). Technical Field

[0003] The invention relates to a lithium-doped silicon-based oxide negative electrode active material, a preparation method thereof, and a negative electrode and a lithium secondary battery containing the same. Background Art

[0004] With the emergence of global warming, a modern social problem, the demand for environmentally friendly technologies to cope with this problem has increased rapidly. In particular, with the increase in technical requirements for electric vehicles and energy storage systems (ESS), the demand for lithium secondary batteries as energy storage devices is surging. Therefore, research is being conducted to improve the energy density of lithium secondary batteries.

[0005] However, conventional commercial secondary batteries generally use graphite active materials such as natural graphite and artificial graphite, but have low energy density due to the low theoretical capacity of graphite, and therefore, research is being conducted to improve energy density by developing a new negative electrode material.

[0006] As a solution, a Si-based material with a high theoretical capacity (3580 mAh / g) has emerged. However, due to the large volume expansion (~400%) during repeated charging and discharging, the Si-based material itself has the disadvantage of deteriorating battery life characteristics. Therefore, as a method to solve the problem of large volume expansion of Si materials, SiO with a low volume expansion rate compared to Si has been developed. x Materials. Although SiO x The material exhibits excellent life characteristics due to its low volume expansion rate, but due to the SiO x The unique low initial coulombic efficiency (ICE) of the material caused by the initial formation of the irreversible phase makes it difficult to apply it to lithium secondary batteries in practice. Summary of the invention

[0007] Embodiments of the present invention are intended to improve the problem of degradation of battery stability, life characteristics, etc. caused by expansion of silicon-based oxide particles due to use of silicon-based oxide as a negative electrode active material by controlling the crystallinity of silicon-based oxide.

[0008] Another embodiment of the present invention aims to improve the problem of initial efficiency degradation caused by the formation of irreversible phases during the initial charge and discharge of silicon-based oxide batteries by introducing a Li pretreatment process.

[0009] Another embodiment of the present invention aims to improve the following problems by performing Li pretreatment under specific conditions: the problems that need more optimization caused by improving the initial efficiency of silicon-based compounds through lithium pretreatment (specifically, (1) the energy cost during Li pretreatment, and (2) the problem of optimizing the capacity characteristics by adjusting the ratio between specific reversible phases and specific irreversible phases in the lithium silicate formed through Li pretreatment).

[0010] Another embodiment of the present invention relates to improving the problem of increased crystallinity of silicon-based oxides corresponding to the problem of improving the initial efficiency of silicon oxides through Li pretreatment by preparing raw materials of silicon oxide under specific conditions and performing a Li pretreatment process under specific conditions.

[0011] In a general aspect, a negative electrode active material includes: negative electrode active material particles, the negative electrode active material particles including: silicon oxide (SiO x , 0 < x ≤ 2), and at least one lithium silicate selected from Li 2 SiO 3 , Li 2 Si 2 O 5 and Li 4 SiO 4 in at least a part of the silicon oxide, wherein when the signal generated in the region of 200 - 600 cm -1 is deconvoluted into three peaks according to Raman spectroscopy, and the peaks are set as peak A, peak B, and peak C respectively from the lowest to the highest in terms of the absolute value of the wave number, the negative electrode active material particles satisfy the following relational expression 1:

[0012] [Relational expression 1]

[0013] 0.3 ≤ D (= C’ / B’ - C” / B”) ≤ 1.0

[0014] wherein, D is the difference between the peak area ratio (C” / B”) and the peak intensity ratio (C’ / B’),

[0015] the peak intensity ratio (C’ / B’) is the ratio of the intensity of peak C to the intensity of peak B,

[0016] the peak area ratio (C” / B”) is the ratio of the area of peak C to the area of peak B.

[0017] The negative electrode active material particles may further satisfy the following equation 2:

[0018] [Equation 2]

[0019] 2.0≤Peak intensity ratio (C' / B')≤3.0

[0020] The peak intensity ratio (C' / B') is the ratio of the intensity of peak C to the intensity of peak B.

[0021] The negative electrode active material particles may further satisfy the following equation 3:

[0022] [Equation 3]

[0023] 1.0≤Peak area ratio (C” / B”)≤3.0

[0024] The peak area ratio (C" / B") is the ratio of the area of ​​peak C to the area of ​​peak B.

[0025] The negative electrode active material particles may include 10 to 100 wt % of the lithium silicate relative to the total weight.

[0026] The negative electrode active material particles may have a peak area ratio H / I according to X-ray diffraction analysis of less than 5.54 (H is the Li 2 Si 2 O 5 The peak area is 26.9 ± 0.3° in the X-ray diffraction analysis. 2 SiO 3 peak area).

[0027] The negative electrode active material particles may have a peak area ratio G / H according to X-ray diffraction analysis of less than 45.99 (G is the area of ​​the Si peak located at 28.4±0.3° in the X-ray diffraction analysis, and H is the area of ​​the Li peak located at 24.9±0.3° in the X-ray diffraction analysis). 2 Si 2 O 5 peak area).

[0028] The negative electrode active material particles may have a peak area ratio G / I according to X-ray diffraction analysis of less than 8.75 (G is the area of ​​the Si peak located at 28.4±0.3° in the X-ray diffraction analysis, and I is the area of ​​the Li peak located at 26.9±0.3° in the X-ray diffraction analysis). 2 SiO 3 peak area).

[0029] The negative active material particles may have a peak area ratio G / I according to X-ray diffraction analysis of less than 1.1.

[0030] Based on the total weight, the negative electrode active material particles may contain 25 wt% or less of Li 4 SiO 4 .

[0031] Based on the total weight, the negative electrode active material may contain 50 wt% or more of the negative electrode active material particles.

[0032] In another general aspect, a method for preparing a negative electrode active material includes: preparing silicon compound particles including a silicon compound; mixing the silicon compound particles with a Li precursor and performing a heat treatment to prepare negative electrode active material particles, the negative electrode active material particles containing silicon oxide (SiO x , 0 < x ≤ 2), and at least one lithium silicate selected from Li 2 SiO 3 , Li 2 Si 2 O 5 , and Li 4 SiO 4 in at least a part of the silicon oxide.

[0033] In another general aspect, a negative electrode includes: a negative electrode active material layer including a negative electrode active material and a water-based binder.

[0034] In yet another general aspect, a lithium secondary battery includes: a negative electrode; a positive electrode; a separator located between the negative electrode and the positive electrode; and an electrolyte.

[0035] Other features and aspects will become apparent through the following detailed description, drawings, and claims. Description of the Drawings

[0036] Figure 1 A diagram showing the results of deconvoluting the Raman spectroscopic analyses of Example 1-1, Example 1-3, and Example 1-5 and Comparative Example 1-2 into three peaks.

[0037] Figure 2 A diagram of the X-ray diffraction analyses of Example 1-1, Example 1-3, Example 1-5, and Example 1-6 and Comparative Example 1-2.

[0038] Figure 3 A diagram of the Raman spectroscopic analyses of the surface and cross-section of the negative electrode prepared from Example 1-5-1 to Example 1-5-4. Detailed Description

[0039] Advantages and features of the present invention and methods for realizing them will be clarified in exemplary embodiments described in detail below with reference to the accompanying drawings. However, the present invention is not limited to the exemplary embodiments disclosed below, but will be implemented in various forms. The exemplary embodiments of the present invention are provided to make the disclosure of the present invention clearer, so that those skilled in the art can easily understand the scope of the present invention. Therefore, the present invention will be defined by the scope of the appended claims. A detailed description for implementing the present invention will be provided below with reference to the accompanying drawings. Regardless of the drawings, the same reference numerals denote the same components, and "and / or" includes each and all combinations of one or more of the recited items.

[0040] Unless otherwise defined herein, all terms (including technical and scientific terms) used in the specification may have the meanings commonly understood by those skilled in the art. Throughout this specification, unless there is a clear description to the contrary, "including" any element will be understood to imply further including other elements rather than excluding any other elements. Additionally, unless explicitly described to the contrary, the singular forms herein include the plural forms.

[0041] In this specification, it will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" or "above" another element, it may be directly on the other element or there may also be intervening elements.

[0042] Embodiments of the present invention provide a negative electrode active material. The negative electrode active material includes negative electrode active material particles, and the negative electrode active material particles include: silicon oxide (SiO x , 0 < x ≤ 2), and at least one lithium silicate selected from Li 2 SiO 3 , Li 2 Si 2 O 5 and Li 4 SiO 4 in at least a part of the silicon oxide.

[0043] The negative electrode active material includes negative electrode active material particles containing silicon oxide, thereby increasing the battery capacity. In addition, the lithium silicate can inhibit the initial formation of an irreversible phase of the silicon oxide during initial charge and discharge.

[0044] When the signal generated in the region of 200 - 600 cm -1 is deconvolved into three peaks according to Raman spectroscopy, and the peaks are set as peak A, peak B, and peak C from the lowest to the highest absolute value of the wave number, the negative electrode active material particles are characterized by satisfying the following relational expression 1:

[0045] [Relational expression 1]

[0046] 0.3 ≤ D (=C' / B'- C” / B”) ≤ 1.0

[0047] Wherein, D is the difference between the peak area ratio (C” / B”) and the peak intensity ratio (C' / B'), the peak intensity ratio (C' / B') is the ratio of the intensity of peak C to the intensity of peak B, and the peak area ratio (C” / B”) is the ratio of the area of ​​peak C to the area of ​​peak B.

[0048] Peak A is the peak with the lowest wave number among the above three peaks, and may be broadened in the amorphous region in the ternary phase including elements other than silicon (Si) and oxygen (O) contained in the material (e.g., Li). Peak B may be derived from the ternary phase of the unreacted material and the amorphous SiO x The peak C may be a signal of amorphous or crystalline matter originating from silicon (Si) particles contained in the material. Specifically, when the resolution peak C is located at 500 cm -1 ±15cm -1 When it is located above 500 cm -1 ±15cm -1 The following regions may be derived from amorphous silicon, amorphous SiO x , or amorphous silicon of lithium silicate.

[0049] At the same time, when the peak C is located at 500 cm -1 ±15 cm -1 When the peak C represents a crystalline phase, only the peak C among the peaks A, B and C has the characteristics of the crystalline phase, so the peak C shows a higher intensity in a narrower area, and the peaks A and B representing the relatively amorphous state are distributed in a wider area with lower peak intensity. Therefore, when the peak C represents the crystalline phase, its shape is often more prominent than the peaks A and B. Usually, in Raman spectroscopy analysis, etc., the crystalline material has a sharp peak characteristic, while the amorphous material has a wide peak characteristic. Due to the peak characteristics of such crystalline and amorphous materials, the peak C of the crystalline material tends to have a peak intensity change that is larger than the peak area change. Therefore, this means that the difference between the peak area ratio (C" / B") and the peak intensity ratio (C' / B') increases, and the growth of the c-Si of the material is accelerated.

[0050] However, when the resolution peak C is located at 500 cm -1 ±15 cm -1In the region below, peaks A, B, and C all have amorphous phase characteristics, and all peaks show peak characteristics of an amorphous phase having low peak intensity in a large region, and therefore, the area and intensity of peak C vary at similar levels to other peaks. Therefore, the difference between the peak area ratio (C" / B") and the peak intensity ratio (C' / B') is reduced, and the growth of c-Si of the material is suppressed, thereby increasing the content of a-Si. This can be considered to be a confirmation that SiO x The crystallization of particles is an indicator of improvement.

[0051] Preferably, the negative electrode active material particles may satisfy 0.3≤D≤1.0, preferably 0.4≤D≤0.8 in Relational Formula 1. When D is less than the lower limit in Relational Formula 1, this means that Li pretreatment cannot be fully performed, and battery performance (such as initial efficiency and life characteristics) may decrease. When D is greater than the upper limit, this means that the growth of c-Si is accelerated, due to SiO x Crystallization of particles leads to degradation of battery performance.

[0052] Meanwhile, a crystalline material refers to a material in which the shape of the single silicon inside the particle is crystalline, while an amorphous material refers to a material in which the shape of the single silicon inside the particle is amorphous or fine particles, which are so small that it is difficult to measure the size by the Scherrer equation in the XRD analysis method, but this does not mean that the lithium silicate is amorphous or fine particles.

[0053] The negative electrode active material particles may further satisfy the following equation 2:

[0054] [Equation 2]

[0055] 2.0≤Peak intensity ratio (C' / B')≤3.0

[0056] The peak intensity ratio (C' / B') is the ratio of the intensity of peak C to the intensity of peak B.

[0057] In relational equation 2, the negative electrode active material particles may satisfy 2.0≤peak intensity ratio (C' / B')≤2.9, or 2.0≤peak intensity ratio (C' / B')≤2.8, more preferably 2.1≤peak intensity ratio (C' / B')≤2.7, or 2.1≤peak intensity ratio (C' / B')≤2.6, and most preferably 2.2≤peak intensity ratio (C' / B')≤2.3. Therefore, the above effect can be further improved.

[0058] The negative electrode active material particles may further satisfy the following equation 3:

[0059] [Equation 3]

[0060] 1.0≤Peak area ratio (C” / B”)≤3.0

[0061] The peak area ratio (C" / B") is the ratio of the area of ​​peak C to the area of ​​peak B.

[0062] In relational equation 3, the negative electrode active material particles may satisfy 1.0≤peak area ratio (C" / B")≤2.5, or 1.2≤peak area ratio (C" / B")≤2.2, more preferably 1.3≤peak area ratio (C" / B")≤2.0, or 1.3≤peak area ratio (C" / B")≤1.8, and most preferably 1.3≤peak area ratio (C" / B")≤1.5, or 1.4≤peak area ratio (C" / B")≤1.5. Therefore, the above effect can be further improved.

[0063] The negative electrode active material particles may contain 10 to 100 wt % of lithium silicate in at least a portion of the particles, and specifically preferably contain 30 to 90 wt %, or 50 to 90 wt % of lithium silicate, relative to the total weight.

[0064] In addition, in order to achieve the above purpose, the negative electrode active material particles preferably satisfy the relationship of the peak area ratio H / I according to the X-ray diffraction analysis method of less than 5.54. Specifically, the peak area ratio H / I can be 4 or less or 3 or less, preferably 2.5 or less, 2.3 or less, or 2 or less, more preferably 1.5 or less, 1.0 or less, or 0.55 or less, and the maximum is preferably 0.4 or less, 0.3 or less, 0.1 or less, or 0.08 or less. The lower limit of the peak area ratio H / I is not particularly limited, but can be 0.00 or more, or 0.01 or more.

[0065] H is Li located at 24.9±0.3° in X-ray diffraction analysis 2 Si 2 O 5 The peak area is 26.9 ± 0.3° in the X-ray diffraction analysis. 2 SiO 3 When the peak area ratio H / I is within this range, it is likely to form a Li 2 Si 2 O 5 Compared with the lithium silicate phase, the formation of Li 2 SiO 3 The phase consumes less Si, which can improve the capacity characteristics and reduce the drastic volume change of Si during the cycle, which is beneficial to improve the life characteristics. 4 SiO 4 The phase has a high moisture content and high reactivity, making it difficult to adjust the physical properties of the slurry in the manufacture of an electrode, and therefore, this is not preferred.

[0066] In addition, the peak area ratio G / H of the negative electrode active material particles according to the X-ray diffraction analysis method may be less than 45.99, specifically, it may be 40 or less or 35 or less, preferably 30 or less, 25 or less, or 20 or less, more preferably 15 or less, or 12 or less, or 10 or less, most preferably 9.5 or less, or 9 or less, or 8.5 or less, or 8.4 or less. The lower limit of the peak area ratio G / H is not particularly limited, and may be 0.00 or more, or 0.3 or more.

[0067] G is the area of ​​the Si peak located at 28.4±0.3° in the X-ray diffraction analysis, and H is the area of ​​the Li peak located at 24.9±0.3° in the X-ray diffraction analysis. 2 Si 2 O 5 The area of ​​the peak.

[0068] In addition, in the X-ray diffraction analysis method, the negative electrode active material particles can further satisfy the peak area ratio G / I less than 8.75, specifically less than 1.35 or 1.09. The lower limit of the peak area ratio G / I is not particularly limited and can be greater than 0, or greater than 0.2.

[0069] G is the area of ​​the Si peak located at 28.4±0.3° in the X-ray diffraction analysis, and I is the area of ​​the Li peak located at 26.9±0.3° in the X-ray diffraction analysis. 2 SiO 3 When the peak area ratio G / I is within this range, Li 2 SiO 3 , while suppressing the growth of c-Si of the negative electrode active material particles, and is therefore preferred.

[0070] The negative electrode active material particles may include 25 wt % or less, preferably 10 wt % or less, more preferably 5 wt % or less, and more preferably less than 1 wt % of Li 4 SiO 4 . 4 SiO 4 The phase has irreversible properties for Li ions and is easily affected by moisture, so it is not preferred as a negative electrode active material using a water-based binder, and preferably does not contain Li 4 SiO 4 phase to prepare a stable slurry. From the perspective of improving the water resistance of the negative electrode slurry, Li 4 SiO 4 The content of is preferably within the above range.

[0071] Based on the total weight of the negative electrode active material, the negative electrode active material particles can be included in an amount of 50% by weight or more, preferably 60% by weight or more, or 70% by weight or more, more preferably 80% by weight or more, or 90% by weight or more, and as an example, in an amount of 100% by weight. Conventionally, when only silicon oxide particles are used as the negative electrode active material, excellent life characteristics cannot be achieved due to the expansion of the electrode volume. Therefore, a graphite-based active material or the like that can mitigate the shrinkage / swelling of the silicon oxide-based particles is mixed and used in an amount of more than half. Since the Li pretreatment of silicon oxide can suppress the generation of crystalline c-Si and increase the proportion of a-Si, the present invention can provide a negative electrode active material by containing silicon oxide and Li in a high content. 2 SiO 3 Thus, compared with the prior art, the initial efficiency and life characteristics can be improved, and at the same time, the discharge capacity can be further increased.

[0072] The average particle diameter of the negative electrode active material particles can be less than 30 μm and greater than 2 μm, preferably less than 10 μm and greater than 7 μm. Within this range, the volume expansion of the negative electrode active material particles during the insertion / extraction of Li ions can be reduced, thereby suppressing electrode deterioration.

[0073] The average particle diameter of the negative electrode active material particles can refer to D50, and D50 refers to the particle diameter at which the cumulative volume accumulated from the smallest particles is 50% when measuring the particle size distribution by the laser scattering method. Here, for D50, a sample of the negative electrode active material particles used for preparation can be collected according to the KSA ISO 13320-1 standard, and the particle size distribution can be measured using a Mastersizer 3000 from Malvern Panalytical Ltd. After dispersing the particles in ethanol as a solvent (if necessary, an ultrasonic disperser can be used), the volume density is measured.

[0074] Another embodiment of the present invention provides a method for preparing a negative electrode active material. When the signal generated in the region of 200 - 600 cm -1 is deconvolved into three peaks, and the peaks are set as peak A, peak B, and peak C from the lowest to the highest absolute value of the wave number, the negative electrode active material particles are characterized by satisfying the following relational expression 1. The method for preparing the negative electrode active material includes: mixing silicon compound particles with a Li precursor and performing heat treatment to prepare negative electrode active material particles, which contain silicon oxide (SiO x , 0 < x ≤ 2), and selected from Li 2 SiO 3 , Li 2 Si2 O 5 and Li 4 SiO 4 at least one lithium silicate in

[0075] First, when preparing silicon compound particles, raw material powders are mixed and heat-treated to prepare silicon compound particles. The mixed raw material powders can be mixed by appropriately adjusting the mixing ratio of Si powder and SiO 2 powders, so as to form the prepared silicon compound particles (SiO x , with a molar ratio of Si and O of 0 < x ≤ 2), but the present invention is not limited thereto.

[0076] Subsequently, the mixed raw material powders can be placed in a furnace under an inert atmosphere and heat-treated at a temperature below 900 °C, preferably below 800 °C or 500 - 700 °C, more preferably 500 - 650 °C, under reduced pressure for 1 - 12 hours or 1 - 8 hours. Conventionally, in order to prepare silicon compound particles, heat treatment is carried out at a high temperature of 900 - 1600 °C, but in the case of SiO x materials or SiO materials, c-Si seeds grow at a heat treatment temperature of 800 °C or higher, and microcrystals grow significantly around 900 °C. Therefore, in the present invention, the formation of c-Si seeds and the growth of c-Si are suppressed, thereby preparing an amorphous or microcrystalline silicon-based compound.

[0077] The prepared silicon compound can be extracted, pulverized, and powdered to prepare silicon compound particles.

[0078] In addition, a carbon layer can be further formed on the surface of the prepared silicon compound particles. In this case, a hydrocarbon gas is introduced into the furnace, and heating can be carried out under reduced pressure or an inert gas at a temperature lower than the heat treatment temperature for preparing the silicon compound. Specifically, the heat treatment can be carried out at a temperature lower than 800 °C or 500 - 700 °C, more preferably at 500 - 650 °C, for 1 - 12 hours or 1 - 8 hours. Conventionally, heat treatment is carried out at a relatively high temperature of 800 - 1200 °C or 800 - 950 °C to coat a carbon material on the surface of the silicon compound particles, but in this case, the disproportionation reaction of the silicon compound is accelerated due to the additional heat treatment, thereby dividing the region into Si and SiO x (0 < x < 2) or SiO 2In the region, it is analyzed that in the silicon compound material, the growth of c-Si is promoted at temperatures above 800 °C, and the size of Si microcrystals is increased. The feature of the present invention is that the size of Si microcrystals is immeasurable, thus greatly suppressing the growth of c-Si. When using the amorphous or microcrystalline silicon-based compound of the present invention, even when Li pretreatment is carried out under the same conditions, compared with the silicon-based compound of microcrystals grown in the conventional technology, the growth of c-Si can be suppressed at a very high level.

[0079] Preferably, a hydrocarbon gas having 3 or less carbon atoms is used as the hydrocarbon gas because it reduces the production cost and can form a good coating, but the present invention is not limited thereto.

[0080] Subsequently, a Li pretreatment process is carried out. It is characterized in that the prepared silicon compound particles and a Li precursor are mixed and heat-treated to prepare negative electrode active material particles, which include silicon oxide (SiO x , 0 < x ≤ 2), and at least one lithium silicate selected from Li 2 SiO 3 , Li 2 Si 2 O 5 and Li 4 SiO 4 in at least a part of the silicon oxide.

[0081] Specifically, it is preferable to carry out the mixing of the silicon compound particles and the Li precursor such that the Li / Si molar ratio is greater than 0.3 and less than or equal to 1.0, specifically greater than 0.3 and less than or equal to 0.8, preferably 0.4 - 0.8, more preferably 0.5 - 0.8, and most preferably 0.6 - 0.8. Within this mixing range, the optimal ratio of Li 2 SiO 3 and Li 2 Si 2 O 5 can be found, and the formation of c-Si and Li 4 SiO 4 can be suppressed, thereby greatly improving the electrochemical performance of the battery.

[0082] As the Li precursor, at least one or more selected from LiOH, Li, LiH, Li 2 O and Li 2 CO 3 can be used, and there is no particular limitation on the compound as long as it can be decomposed during the heat treatment.

[0083] Subsequently, the compound can be heat-treated at a temperature higher than 500 °C and lower than 700 °C for 1 - 12 hours in an inert atmosphere. When the heat treatment is carried out at a temperature above 700 °C, a disproportionation reaction occurs or the growth of Si crystals is accelerated, inevitably growing c-Si. And when the raw material is prepared at a temperature lower than 700 °C, the crystal growth is inhibited, and thus amorphous or microcrystalline silicon oxide particles can be prepared. In addition, when the heat treatment is carried out at a low temperature below 500 °C, the effect of lithium pretreatment rapidly decreases, and thus the effect of suppressing the growth of the crystalline phase of silicon oxide particles by low-temperature heat treatment according to the present invention is not shown. Meanwhile, in the Li pretreatment by an electrochemical method or a redox method, Li 4 SiO 4 , which is a lithium silicate, may be produced. However, according to the present invention, target lithium silicates with different compositions can be synthesized with high purity by heat treatment.

[0084] Meanwhile, for the inert atmosphere, known methods in which the inside of the reaction unit is purged with an inert gas to form an inert atmosphere can be applied, and the inert gas can be selected from Ne, Ar, Kr, N 2 etc. Preferably, it can be Ar or N 2 , but the present invention is not limited thereto.

[0085] Subsequently, the heat-treated product is recovered and pulverized to prepare a negative electrode active material including final negative electrode active material particles, but the present invention is not limited thereto. Any known pulverization method can be applied, but the present invention is not limited thereto.

[0086] Another embodiment provides a negative electrode for a lithium secondary battery, which includes: a current collector; and a negative electrode active material layer located on the current collector, and the negative electrode active material layer includes a negative electrode active material and a water-based binder.

[0087] The current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof, but is not limited thereto.

[0088] The negative electrode active material layer includes a negative electrode active material and a water-based binder, and optionally, a conductive material can be further included.

[0089] The negative electrode active material includes negative electrode active material particles, and the negative electrode active material particles include: silicon oxide (SiO x , 0 < x ≤ 2), and selected from Li 2 SiO 3 , Li 2 Si 2 O 5 and Li4 SiO 4 at least one lithium silicate, and optionally, may further include a substance that allows reversible insertion / extraction of lithium ions, lithium metal, an alloy of lithium metal, a substance that can be doped with or de-doped with lithium, or a transition metal oxide.

[0090] The negative electrode active material particles are as described above.

[0091] Examples of substances that allow reversible insertion / extraction of lithium ions include carbon materials, that is, carbon-based negative electrode active materials commonly used in lithium secondary batteries. Representative examples of carbon-based negative electrode active materials include crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon include graphite such as natural graphite or artificial graphite in the form of amorphous, plate-like, flaky, spherical, or fibrous, and examples of amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.

[0092] The alloy of lithium metal can be an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0093] The material that can be doped with or de-doped with lithium can be a silicon-based material, for example, Si, SiO x (0 < x < 2), Si-Q alloy (Q is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Si-carbon composite; Sn, SnO 2 , Sn-R alloy (R is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn-carbon composite, etc., and at least one of them and SiO 2 mixture can also be used. The elements Q and R can be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0094] The transition metal oxide can be lithium titanium oxide.

[0095] The negative electrode active material may contain negative electrode active material particles in an amount of 50 wt % or more, preferably 60 wt % or more or 70 wt % or more, more preferably 80 wt % or more or 90 wt %, and 100 wt % as an example, relative to the total weight of the negative electrode active material.

[0096] The water-based binder is used to bind the negative electrode active material particles to each other and to adhere the negative electrode active material to the current collector well. The water-based binder can be polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, various copolymers thereof, etc. Specifically, the binder can include a binder formed by carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and a mixture thereof.

[0097] The conductive material is used to impart conductivity to the electrode, and any conductive material can be used as long as it is a conductive material and does not cause chemical changes in the battery to be constructed. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fiber; metal-based materials such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0098] The contents of the binder and the conductive material in the negative electrode active material layer may each be 1 wt % to 10 wt %, preferably 1 wt % to 5 wt %, relative to the total weight of the negative electrode active material layer, but is not limited thereto.

[0099] Another embodiment provides a lithium secondary battery including: a negative electrode; a positive electrode; a separator between the negative electrode and the positive electrode; and an electrolyte.

[0100] The negative electrode is as described above.

[0101] The positive electrode includes a positive electrode active material layer formed by coating a positive electrode slurry including a positive electrode active material on a current collector.

[0102] The current collector may be the negative electrode current collector described above, and any material known in the art may be used, but the present invention is not limited thereto.

[0103] The positive electrode active material layer includes a positive electrode active material, and optionally, may further include a binder and a conductive material. The positive electrode active material may be any known positive electrode active material in the art, for example, preferably a composite oxide of lithium and a metal selected from cobalt, manganese, nickel and a combination thereof. The present invention is not limited thereto.

[0104] The binder and the conductive material may be the above-mentioned binder and negative electrode conductive material, and any material known in the art may be used, but the present invention is not limited thereto.

[0105] The separator may be selected from glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene or a combination thereof, and may be in the form of a nonwoven or woven fabric. For example, in a lithium secondary battery, a polyolefin-based polymer separator such as polyethylene or polypropylene may be used, a separator coated with a composition containing a ceramic component or a polymer material for ensuring heat resistance or mechanical strength may be used, optionally, a single layer or multilayer structure may be used, and any separator known in the art may be used, but the present invention is not limited thereto.

[0106] The electrolyte includes an organic solvent and a lithium salt.

[0107] The organic solvent is used as a medium in which ions participating in the electrochemical reaction of the battery can move, for example, a carbonate-based solvent, an ester-based solvent, an ether-based solvent, a ketone-based solvent, an alcohol-based solvent or an aprotic solvent can be used, and the organic solvent can be used alone or in combination of two or more, and when two or more are used in combination, the mixing ratio can be appropriately adjusted according to the desired battery performance. At the same time, any organic solvent known in the art can be used, but the present invention is not limited thereto.

[0108] Lithium salts are dissolved in organic solvents and serve as a source of lithium ions in batteries to allow basic operation of lithium secondary batteries, and are substances that facilitate the movement of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts include LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiN(SO 3 C 2 F 5 ) 2 、LiN(CF 3 SO 2 ) 2 ,LiC 4 F 9 SO 3 、LiClO 4 、LiAlO 2 、LiAlCl4 、LiN(C x F 2x+ 1 SO 2 )(C y F 2y+1 SO 2 ) (x and y are natural numbers), LiCl, LiI, LiB(C 2 O 4 ) 2 or a combination thereof, but the present invention is not limited thereto.

[0109] The concentration of the lithium salt may be in the range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within this range, the electrolyte has appropriate conductivity and viscosity, so that the electrolyte can exhibit excellent electrolyte performance and lithium ions can move efficiently.

[0110] In addition, in order to improve the charge and discharge characteristics, flame retardant properties, etc., the electrolyte may further contain pyridine, triethyl phosphate, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum chloride, etc., as needed. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride and ethylene trifluoride may be further included, and in order to improve the conservation property at high temperatures, fluoroethylene carbonate (FEC), propylene sulfone (PRS), fluoropropylene carbonate (FPC), etc. may be further included.

[0111] The manufacturing method of the lithium secondary battery according to the present invention for achieving the above-mentioned purpose may include stacking the manufactured negative electrode, separator and positive electrode in this order to form an electrode assembly, placing the prepared electrode assembly in a cylindrical battery case or an angled battery case (angled battery case), and then injecting an electrolyte. In addition, a lithium secondary battery can be manufactured by stacking electrode assemblies and immersing the assembly in an electrolyte to obtain a product, which is then placed in a battery case and sealed.

[0112] As the battery case used in the present invention, those commonly used in the art can be used, and the appearance is not limited by the battery use. For example, a cylindrical, square, pouch, or coin shape can be used.

[0113] The lithium secondary battery according to the present invention can be used in a battery cell used as a power source for a small device, and can also be preferably used as a unit cell in a medium or large battery module including a plurality of battery cells. Preferred examples of medium or large devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, systems for power storage, etc., but are not limited thereto.

[0114] Hereinafter, preferred examples and comparative examples of the present invention will be described. However, the following examples are merely preferred exemplary embodiments of the present invention, and the present invention is not limited thereto.

[0115] Example

[0116] [Examples 1-1 to 1-7 and Comparative Examples 1-1 and 1-4]

[0117] Preparation of silicon compound particles

[0118] A raw material in which metal silicon (silicon metal) and silicon dioxide are mixed is introduced into a reaction furnace and evaporated in an atmosphere with a vacuum degree of 10 Pa to obtain a product, which is deposited on a suction cup and sufficiently cooled, and the deposit is taken out and pulverized with a ball mill. In the silicon compound particles thus obtained, SiO x x is 1.0. Next, the particle size of the silicon compound particles is adjusted by grading. After that, pyrolysis CVD is performed to coat the carbon material on the surface of the silicon compound particles. The average thickness of the carbon material is 100 nm. The silicon compound obtained is SiO particles with an average particle size (D50) of 8 μm. Here, (1) the temperature (heat treatment temperature) and heat treatment time of the reaction furnace in the preparation of the silicon compound particles, and (2) the temperature (heat treatment temperature) and heat treatment time of the reaction furnace when the carbon material is coated on the surface of the silicon compound particles are applied as described in Example 1-1 of Table 4 below.

[0119] Preparation of negative electrode active material

[0120] The prepared silicon compound particles and LiOH powder were mixed to form a mixed powder, and the mixed powder and zirconium oxide balls (1-20 times of the mixed powder) were placed in an airtight container and shaken and mixed for 30 minutes using a shaker. After that, the mixed powder was filtered using a 25-250 μm sieve and then placed in an aluminum crucible.

[0121] The aluminum crucible was heat treated in a furnace under a nitrogen atmosphere for 1-12 hours. Subsequently, the heat-treated powder was recovered and pulverized in a mortar to prepare a x ) and lithium silicates (e.g. Li 2 Si 2 O 5 and Li2 SiO 3 Here, the heat treatment temperature in the preparation of the negative electrode active material particles and the molar ratio of Li / Si in the mixture of the silicon compound and the LiOH powder are summarized in Table 1 below.

[0122] The prepared negative electrode active material particles were used in an amount of 100 wt % relative to the total weight of the negative electrode active material to prepare a negative electrode active material.

[0123] Negative electrode manufacturing

[0124] The prepared negative electrode active material, conductive material carbon black (super P) and water-based binder (polyacrylic acid) are dispersed in an aqueous solution at a weight ratio of 8:1:1, coated on a copper foil, and vacuum dried at 80-160° C. for 1-24 hours to prepare a negative electrode.

[0125] Preparation of half-cell

[0126] Using the prepared negative electrode and lithium metal as a counter electrode, a PE separator was inserted between the negative electrode and the counter electrode, and an electrolyte was injected to assemble a button cell (CR2032). The assembled button cell was paused at room temperature for 3-24 hours to prepare a half-cell.

[0127] Here, the electrolyte was obtained by mixing lithium salt 1.0 M LiPF6 with an organic solvent (EC:EMC = 3:7 volume %) and mixing 2 volume % of an electrolyte additive FEC.

[0128] Evaluation example

[0129] 1. Analysis of the crystallinity of negative electrode active material particles by Raman spectroscopy

[0130] For Raman spectroscopy analysis, an Invia confocal Raman microscope purchased from Renishaw (UK) was used in static mode at a laser wavelength of 532 nm and a lens magnification of 50 times in the range of 67–1800 cm -1 The surface of the particle was measured 8 times within a range of , and the average value was used.

[0131] From 200cm -1 Up to 600cm -1The analysis results of the Raman spectrum were obtained to confirm the area ratio and intensity ratio of each peak, wherein the resolution peaks obtained by deconvolving each signal into three peaks using a Gaussian model under an R-square condition of 0.987 or above were set as Peak 1, Peak 2, and Peak 3 from the lowest to the highest wave number, respectively, the peak positions were set as A, B, and C, the peak intensities were set as A', B', and C', and the peak areas were set as A", B", and C", which are summarized in the following Tables 1 and 2.

[0132] 2. Analysis of the lithium silicate composition formed in the silicon oxide particles by X-ray diffraction analysis

[0133] For XRD analysis, an Empyrean XRD diffractometer purchased from PANalytical was used, and measurements were performed by applying a current of 40 mA and a voltage of 45 kV. 2 SiO 3 )、98-028-0481 (Li 2 Si 2 O 5 )、98-003-5169 (Li 4 SiO 4 ) were compared to analyze each phase. Based on the obtained results, the peak positions of Si (111) at 28.4±0.3°, Li (111) at 24.9±0.3°, 2 Si 2 O 5 The peak position of (111) and the Li 2 SiO 3 The peaks thus obtained are deconvoluted to determine the area G corresponding to (111) of Si, the area G corresponding to (111) of Li, and the area G corresponding to (111) of Si. 2 Si 2 O 5 The area H of (111) and the corresponding Li 2 SiO 3 The area I of (111) was calculated and the area ratio was determined. The evaluation results are shown in Table 3 below.

[0134] 3. Analysis of Si crystal size of silicon compounds by X-ray diffraction analysis

[0135] For XRD analysis, an Empyrean XRD diffractometer purchased from PANalytical was used, and the measurement was performed by applying a current of 40 mA and a voltage of 45 kV. Specifically, the half-peak width of the diffraction peak caused by the Si (111) crystal plane (2θ = 28.4 ± 0.3 °) was obtained by X-ray diffraction using Cu-Kα rays. The size of the Si crystal was analyzed using the Scherrer equation.

[0136] Scherrer equation: τ=(Kλ) / (βcosθ)

[0137] K: dimensionless shape factor, 0.9

[0138] λ: X-ray wavelength, 0.1540598nm

[0139] β: Full width at half maximum

[0140] θ: Bragg angle

[0141] 4. Evaluation of electrochemical performance (initial discharge capacity, initial efficiency and life characteristics)

[0142] The prepared half-cell was charged at a constant current at a current rate of 0.1C at room temperature (25°C) until the voltage reached 0.01V (relative to Li), and then charged at a constant voltage at a voltage of 0.01V until the current reached 0.01C rate (cut-off current). The battery was discharged at a constant current rate of 0.1C until the voltage reached 1.5V (relative to Li). This charge and discharge was set as 1 cycle, and 1 charge and discharge cycle was performed in the same manner, and then 50 cycles were performed, in which the applied current was changed to 0.5C during charge and discharge, and a 10-minute pause was made between two cycles.

[0143] The initial discharge capacity, initial efficiency, and life characteristics as a capacity retention rate (%) of the discharge capacity after 50 cycles relative to the discharge capacity after one cycle were measured, and the results are summarized in Table 2 below.

[0144] [Table 1]

[0145]

[0146] [Table 2]

[0147]

[0148] Referring to Tables 1 and 2, the analytical peak corresponding to Peak 1 (peak position A) is not only considered to be a peak corresponding to crystalline Si and amorphous Si, but the amorphous region peak appears to be broad because the ternary phase includes elements other than silicon (Si) and oxygen (O) included in the material (e.g., Li). The analytical peak corresponding to Peak 2 (peak position B) can be interpreted as amorphous SiO derived from the above ternary phase. x The analytical peak corresponding to Peak 3 (peak position C) is the determining factor for distinguishing amorphous silicon and crystalline silicon particles (Si) of the material, and it is determined when the analytical peak is located at 500 cm -1 ±15 cm -1 When the peak is above 500 cm -1 ±15cm -1 In the region below, the peak originates from amorphous Si and amorphous Si of lithium silicate.

[0149] In Examples 1-1, 1-2, and 1-4 to 1-6, since peak C is located at 500 cm -1 ±15cm -1 In addition, although the peak C of Examples 1-3 and 1-7 is located at 500 cm -1 , but the peak area ratio (C" / B") and the peak intensity ratio (C' / B') are within the range of the present invention, so it can be considered that the growth of crystalline c-Si of this material is suppressed and the content of amorphous a-Si phase is high. However, in Comparative Example 1-2, the intensity ratio of Peak C is relatively high relative to the area ratio of Peak C, which promotes the growth of c-Si, and is therefore not a preferred material for the material of the present invention. The same is true for Comparative Example 1-4.

[0150] Meanwhile, the negative electrode active material particles of Examples 1-1 to 1-7 prepared under the conditions of the present invention during Li pretreatment effectively formed a lithium silicate phase on silicon oxide, and Raman spectroscopy analysis showed that the growth of c-Si was suppressed to form a-Si at a high ratio. This result indicates that, as described above, the growth of c-Si was suppressed to increase the a-Si ratio, thereby improving the SiO2 phase during conventional Li pretreatment. x Therefore, the battery performance was improved compared with Comparative Examples 1-1 to 1-4.

[0151] In Comparative Examples 1-2 and 1-4, it was analyzed that the lithium precursor was mixed at too high a content during Li pretreatment, so that the growth of c-Si could not be fully suppressed. In Example 1-7, it can be confirmed that although the same lithium precursor content as in Comparative Example 1-2 was used, the manufactured material stayed in the amorphous region. This means that since the heat treatment temperature is lower than the heat treatment temperature in Comparative Example 1-2, the growth of crystalline material is suppressed. However, in Comparative Examples 1-1 and 1-3, a low content of lithium precursor was mixed, and as a result, the Li pretreatment was not fully performed, and the initial efficiency and life characteristics were deteriorated.

[0152] In addition, in Examples 1-2 and 1-4 or 1-3 and 1-5, although the mixing ratio of the Li precursor is the same, it is found that the crystallinity of Si increases at about 600°C and the life characteristics are not much improved. In particular, in Examples 1-5, since the Li pretreatment is performed at a lower temperature, an amorphous or microcrystalline negative electrode active material can be obtained, and relatively improved capacity and efficiency are shown.

[0153] For Reference Example 1, the maximum peak (peak position C) appears at 472.2 cm -1 This does not mean that the material has a high crystallinity compared to the materials of Example 1-1, Example 1-2, Examples 1-4 to 1-6, and Comparative Example 1-1, but can be interpreted as amorphous or microcrystalline SiO2 that does not contain lithium silicate. x Therefore, when lithium silicate is included in the Li pretreatment, as in the example of Table 1, it should be interpreted that the maximum peak (peak position C) can be shifted to a lower wavenumber range.

[0154] Therefore, it is found that only when the Li precursor and SiO x When the ratio of active materials and temperature are set, a negative electrode active material that inhibits the formation of crystalline Si can be obtained.

[0155] [Table 3]

[0156]

[0157] Referring to Table 3, the negative electrode active material particles of Examples 1-1 to 1-7 prepared under the conditions of the present invention during Li pretreatment can suppress the growth of crystalline Si to form amorphous Si at a high ratio, and may also promote Li 2 SiO 3 The formation of the irreversible phase, in which more Li + The ions react, so they are effective in terms of initial efficiency and lifetime characteristics.

[0158] Meanwhile, in Comparative Example 1-2, when Li pretreatment was performed, the mixing amount of the lithium precursor was slightly larger and the heat treatment temperature was increased, and Li was formed at a high rate. 2 SiO 3 , but it promotes the growth of c-Si, so the life characteristics are not good.

[0159] [Table 4]

[0160]

[0161] (In Table 4, the content of lithium silicate and Li 4 SiO 4 The contents are expressed in wt % relative to the total weight of the negative electrode active material particles.)

[0162] Referring to Tables 1 and 4, it has been confirmed that during Li pretreatment, under the condition of excess Li precursor, c-Si and Li 4 SiO 4 phase, and as mentioned above, c-Si will reduce the life characteristics, and Li 4 SiO 4 The phase has high reactivity with water, so it is difficult to adjust the physical properties of the slurry during electrode production, and is therefore not preferred.

[0163] In addition, as can be seen from Examples 1-4 to 1-7, even when the ratio of the Li precursor is too high, when the pretreatment temperature is lowered, the c-Si and Li 4 SiO 4 phase, but if the content exceeds a certain level, the formation of c-Si and Li 4 SiO 4 The effect of the phase may be reduced.

[0164] [Example 2-1 and Comparative Examples 2-1 to 2-6]

[0165] Negative electrode active material particles were prepared in the same manner as in Example 1-1, except that the preparation of silicon compound particles and coating of the surface with a carbon layer were performed under the conditions described in Table 5. Here, Table 5 summarizes (1) the heat treatment temperature and heat treatment time when preparing silicon compound particles and the crystallite size of the prepared silicon compound particles, (2) the heat treatment temperature and heat treatment time when the surface of the silicon compound particles is coated with a carbon material, the crystallite size of the obtained product, and (3) the Raman spectroscopic analysis results of the negative electrode active material particles pretreated with lithium.

[0166] [Table 5]

[0167]

[0168] Referring to Table 5, in Example 1-1 and Example 2-1, since the heat treatment conditions were adjusted during the preparation of the SiOx-based material and the coating of the surface with the carbon material, the Si crystallite size can be effectively controlled. However, it was found that in Comparative Examples 2-1, 2-2, 2-3, 2-4, 2-5 and 2-6, the size of the Si crystallite formed was larger. Therefore, although the Li pretreatment heat treatment conditions were adjusted within the scope of the present invention, it can be confirmed that the formation of c-Si was not suppressed. From the above results, it can be seen that in order to suppress the SiO x The growth of c-Si in the negative electrode active material particles requires the SiO x SiO2 coated with substrate or carbon material x The Si crystallite size is controlled at a very low level.

[0169] [Example 3-1 to Example 3-5 and Comparative Example 3-1 to Comparative Example 3-5]

[0170] The half-cells of Examples 3-1 to 3-5 and Comparative Examples 3-1 to 3-5 were prepared in the same manner as in Examples 1-4 and Comparative Example 1-1, except that a negative electrode active material having a composition (weight ratio) of natural graphite: negative electrode active material particles (SiOx particles) as shown in Table 6 below was prepared.

[0171] [Table 6]

[0172]

[0173] The negative electrode active material particles prepared in Example 1-4 were mixed with natural graphite as in Example 3-1 to Example 3-5. Even if an excess amount of SiO x This means that the SiO x The volume change will not accelerate the degradation of graphite.

[0174] However, in Comparative Examples 3-1 to 3-5 to which the negative electrode active material particles of Comparative Example 1-1 were applied, it was found that even SiO x and graphite with relatively good volume change due to SiO x The rapid volume change causes electrode degradation, thereby reducing the life characteristics to below expectations.

[0175] 5. Analysis of the crystallinity of the surface and cross-section of the negative electrode active material particles by Raman spectroscopy

[0176] The negative electrode was prepared in the same manner as in Example 1-5, except that natural graphite was prepared: the negative electrode active material (SiO xThe surface and cross-section Raman spectroscopy analysis was performed on the fresh negative electrode (Example 1-5-1 and Example 1-5-2) without electrochemical reaction and the negative electrode after a charge and discharge cycle (Example 1-5-3 and Example 1-5-4), and the results are shown in Table 7 below.

[0177] Meanwhile, one cycle of charge and discharge was performed under the conditions of CC charge (0.1 C, 0.01 V cutoff), CV charge (0.01 V, 0.01 C cutoff), and CC discharge (0.1 C, 1.5 V cutoff). Raman spectroscopy was performed using an Invia confocal Raman microscope purchased from Renishaw (UK) in static mode at a laser wavelength of 532 nm with a lens magnification of 50 times in the range of 67–1800 cm -1 The surface and cross section of the negative electrode were measured 8 times within a range of , and the average value was used.

[0178] [Table 7]

[0179]

[0180] Referring to Table 7, in the Raman spectroscopic analysis of the surface and cross section of the negative electrode of Examples 1-5-1 to 1-5-4, it was confirmed that the D band was at 1340 cm -1 Up to 1350 cm -1 and confirmed that the G band is at 1570 cm -1 Up to 1590 cm -1 This can be explained by the D band and G band caused by the natural graphite active material and carbon conductive material contained in the electrode.

[0181] In addition, the analysis results of the electrode surface showed that the Raman peak position C of the fresh electrode and the electrode after a cycle was located at 450-480 cm -1 This is similar to the results of the powder samples of Examples 1-5. The analysis results of the electrode cross section also confirmed that the Raman peak position C of the fresh electrode and the electrode after the cycle is located at 450-480 cm -1 This is also similar.

[0182] Refer to Table 7 and Figure 3 , it was confirmed that even if the sample prepared in the present invention was manufactured as an electrode and cycled, there was no degeneration such as crystallization of the material and the amorphous state was well maintained.

[0183] The expansion of silicon-based oxide particles can be suppressed to improve battery stability and lifetime characteristics, and silicon-based oxides can be Li pretreated to address initial efficiency degradation issues.

[0184] Additionally, Li pretreatment can be performed under specific conditions to improve the energy cost during Li pretreatment, and the ratio of a specific phase of the formed lithium silicate can be adjusted to optimize the capacity characteristics.

[0185] In addition, since the initial efficiency of silicon oxide is improved by Li pretreatment, the crystallinity of silicon-based oxide (increase in c-Si / a-Si ratio) increases accordingly. However, this problem is solved by preparing the raw materials of silicon oxide and performing Li pretreatment under specific conditions. As a result, the electrochemical performance can be further improved.

[0186] Although the exemplary embodiments of the present invention have been described above, the present invention is not limited to the exemplary embodiments, but can be implemented in various forms that are different from each other, and those skilled in the art will understand that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, it should be understood that the above exemplary embodiments are not restrictive in all aspects, but are exemplary.

Claims

1. A negative electrode active material comprising: Negative active material particles, the negative active material particles comprising: silicon oxide (SiO x , where 0 < x ≤ 2), and at least one lithium silicate selected from Li2SiO3, Li2Si2O5, and Li4SiO4 in at least a part of the silicon oxide Among them, according to the Raman spectrum in the range of 200-600 cm -1 When the signal generated in the region is deconvoluted into three peaks, the peaks A, B and C are set from the lowest to the highest absolute value of the wave number, respectively, and the negative electrode active material particles satisfy the following relationship 1: [Equation 1] 0.3 ≤ D (=C' / B'- C” / B”) ≤ 1.0 in D is the difference between the peak area ratio C” / B” and the peak intensity ratio C' / B', The peak intensity ratio C' / B' is the ratio of the intensity of the peak C to the intensity of the peak B, The peak area ratio C" / B" is the ratio of the area of ​​the peak C to the area of ​​the peak B.

2. The negative electrode active material according to claim 1, wherein The negative electrode active material particles further satisfy the following relationship 2: [Equation 2] 2.0≤Peak intensity ratio (C' / B')≤3.0 The peak intensity ratio C' / B' is the ratio of the intensity of the peak C to the intensity of the peak B.

3. The negative electrode active material according to claim 1, wherein The negative electrode active material particles further satisfy the following relationship 3: [Equation 3] 1.0≤Peak area ratio C” / B”≤3.0 The peak area ratio C" / B" is the ratio of the area of ​​the peak C to the area of ​​the peak B.

4. The negative electrode active material according to claim 1, wherein The negative electrode active material particles include 10-100 wt % of the lithium silicate relative to the total weight.

5. The negative electrode active material according to claim 1, wherein The negative electrode active material particles have a peak area ratio H / I according to X-ray diffraction analysis of less than 5.54, H being the area of ​​the Li2Si2O5 peak located at 24.9±0.3° in the X-ray diffraction analysis, and I being the area of ​​the Li2SiO3 peak located at 26.9±0.3° in the X-ray diffraction analysis.

6. The negative electrode active material according to claim 1, wherein The negative electrode active material particles have a peak area ratio G / H according to X-ray diffraction analysis of less than 45.99, G being the area of ​​the Si peak located at 28.4±0.3° in the X-ray diffraction analysis, and H being the area of ​​the Li2Si2O5 peak located at 24.9±0.3° in the X-ray diffraction analysis.

7. The negative electrode active material according to claim 1, wherein The negative electrode active material particles have a peak area ratio G / I according to X-ray diffraction analysis of less than 8.75, G being the area of ​​the Si peak located at 28.4±0.3° in the X-ray diffraction analysis, and I being the area of ​​the Li2SiO3 peak located at 26.9±0.3° in the X-ray diffraction analysis.

8. The negative electrode active material according to claim 7, wherein The peak area ratio G / I according to X-ray diffraction analysis was less than 1.

1.

9. The negative electrode active material according to claim 1, wherein The negative electrode active material particles contain 25 wt % or less of Li 4 SiO 4 relative to the total weight.

10. The negative electrode active material according to claim 1, wherein The negative electrode active material includes 50 wt % or more of the negative electrode active material particles relative to the total weight.

11. A method for preparing the negative electrode active material according to any one of claims 1 to 10, the method comprising: preparing silicon compound particles; and Mix the silicon compound particles with a Li precursor and perform heat treatment to prepare negative electrode active material particles, the negative electrode active material particles comprising silicon oxide (SiO x , 0 < x ≤ 2), and at least one lithium silicate selected from Li2SiO3, Li2Si2O5, and Li4SiO4 in at least a part of the silicon oxide.

12. A negative electrode, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises: The negative electrode active material and the water-based binder according to any one of claims 1 to 10.

13. A lithium secondary battery comprising: The negative electrode of claim 12; a positive electrode; a separator located between the negative electrode and the positive electrode; and electrolyte.

Citation Information

Patent Citations

  • System and method for local currency transaction

    KR1020200094407A